2020
DOI: 10.1038/s41419-020-02833-y
|View full text |Cite
|
Sign up to set email alerts
|

A novel N6-methyladenosine (m6A)-dependent fate decision for the lncRNA THOR

Abstract: Previous studies have revealed the critical roles of the N6-methyladenosine (m6A) modification of long non-coding RNAs (lncRNAs) in cancers, but the relationship between the oncogenic role of the lncRNA THOR (a representative of cancer/testis lncRNAs) and m6A modification remains unclear. Here, we show that the internal m6A modification of the lncRNA THOR via an m6A-reader-dependent modality regulates the proliferation of cancer cells. Our findings demonstrated that the loss of the lncRNA THOR inhibits the pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
78
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(79 citation statements)
references
References 73 publications
1
78
0
Order By: Relevance
“…It is reported that m6A process was closely associated with lncRNA processing (14). By performing GSEA analysis, we revealed that METTL14 was involved in the process and degradation of ncRNAs (Figure 5A).…”
Section: Mettl14 Suppresses Pyroptosis Via Targeting Tincr Lncrnamentioning
confidence: 78%
“…It is reported that m6A process was closely associated with lncRNA processing (14). By performing GSEA analysis, we revealed that METTL14 was involved in the process and degradation of ncRNAs (Figure 5A).…”
Section: Mettl14 Suppresses Pyroptosis Via Targeting Tincr Lncrnamentioning
confidence: 78%
“…Coker et al found that METTL3 promotes m 6 A modification of XIST, which is recognized by m 6 A reader YTHDC1, leading to X chromosome inactivation ( Coker et al, 2020 ). Liu et al indicated that METTL3 promotes m 6 A modification of lncRNA THOR and cancer cell proliferation ( Liu et al, 2020 ). Another study indicated that lncRNA pncRNA-D suppresses cyclin D1 and arrests cell cycle through RNA m 6 A modification ( Yoneda et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Specific m6A readers YTHDF1 and YTHDF2 can read the highly enriched m6A motif on lncRNA Thor transcripts, regulate its stability, and thus maintain the carcinogenic effect. 46 Interestingly, the two studies of He et al 47 and Chen et al 48 respectively confirmed that ALKBH5 played two opposite effects of promoting cancer and inhibiting cancer in different cancers by regulating different lncRNA levels through demethylation. ALKBH5 inhibits the progression of pancreatic cancer by demethylation of lncRNA KCNK15-AS1, while the up-regulation of lncRNA PVT1 mediated by ALKBH5 promotes the proliferation of osteosarcoma cells in vitro and tumor growth in vivo.…”
Section: M6a Rna Modificationmentioning
confidence: 99%